2021
DOI: 10.2166/washdev.2021.069
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of drinking water quality and sanitary risk levels of water storage in food establishments of Addis Ababa, Ethiopia

Abstract: The study aimed to assess the determinants of drinking-water quality and sanitary risk levels of water storage. An institution-based cross-sectional study was conducted. One hundred and twenty-five drinking-water samples were collected directly from food outlets' drinking-water storages. Observational checklist was used to assess sanitary risk levels of the storages. Data analysis was conducted using multivariable logistic regression. Type of primary source of drinking-water, having continuous piped water, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Contaminated water is linked to the transmission of diseases such as cholera, diarrhea, dysentery, hepatitis A, and typhoid fever. Absent, inadequate, or inappropriately managed drinking water service exposes individuals to preventable health risks [33][34][35]. This is particularly the case in school facilities where both students and staff are placed at additional risk of infection and disease when water is contaminated and sanitation and hygiene services are lacking [36].…”
Section: Discussionmentioning
confidence: 99%
“…Contaminated water is linked to the transmission of diseases such as cholera, diarrhea, dysentery, hepatitis A, and typhoid fever. Absent, inadequate, or inappropriately managed drinking water service exposes individuals to preventable health risks [33][34][35]. This is particularly the case in school facilities where both students and staff are placed at additional risk of infection and disease when water is contaminated and sanitation and hygiene services are lacking [36].…”
Section: Discussionmentioning
confidence: 99%
“…High water temperature enhances the growth of microorganisms and may also cause taste, odour, colour and corrosion problems (Girmay et al 2021;Price et al 2019). Most pathogens require higher temperature to proliferate in the water (Slavik et al 2020;WHO 2021;Gizachew et al 2020).…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…It is also the reality of most slum households of Ethiopia. Studies also indicated that households' poor drinking water handling and storage practices caused microbial contamination of water (Slavik et al 2020;Girmay et al 2021;Sharma et al 2013). In this regard, it is recommended to inspect drinking water delivery systems from source to mouth and "handling of water at home" is one element.…”
Section: Introductionmentioning
confidence: 99%
“…Studies supported that inappropriate water handling and unhygienic activities contribute to drinking water contamination at the point of Environmental Health Insights use. 7,32,33 Therefore, to maintain water safety, it is essential to have household water treatment, safe water handling, storage practices, and improved hygiene. 29,34 The sanitation service ladder starts from the basic service in the surveillance site.…”
Section: Discussionmentioning
confidence: 99%